Nanotechnology in Modern Photodynamic Therapy of Cancer: A Review of Cellular Resistance Patterns Affecting the Therapeutic Response - Elvin Peter Chizenga; Heidi Abrahamse (Pharmaceutics, 2020)
Photodynamic therapy (PDT) has emerged as a potential therapeutic option for most localized cancers. Its high measure of specificity and minimal risk of side effects compared to other therapies has put PDT on the forefront of cancer research in the current era. The primary cause of treatment failure and high mortality rates is the occurrence of cancer resistance to therapy. Hence, PDT is designed to be selective and tumor-specific. However, because of complex biological characteristics and cell signaling, cancer cells have shown a propensity to acquire cellular resistance to PDT by modulating the photosensitization process or its products. Fortunately, nanotechnology has provided many answers in biomedical and clinical applications, and modern PDT now employs the use of nanomaterials to enhance its efficacy and mitigate the effects of acquired resistance. This review, therefore, sought to scrutinize the mechanisms of cellular resistance that affect the therapeutic response with an emphasis on the use of nanomaterials as a way of overriding cancer cell resistance. The resistance mechanisms that have been reported are complex and photosensitizer (PS)-specific. We conclude that altering the structure of PSs using nanotechnology is an ideal paradigm for enhancing PDT efficacy in the presence of cellular resistance.